2010
DOI: 10.1093/eurjhf/hfq032
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous levosimendan vs. dobutamine in acute decompensated heart failure patients on beta‐blockers

Abstract: AimsThe aim of this study is to compare the effects of a 24 h intravenous infusion of levosimendan and a 48 h infusion of dobutamine on invasive haemodynamics in patients with acutely decompensated chronic NYHA class III–IV heart failure. All patients were receiving optimal oral therapy including a β-blocker.Methods and resultsThis was a multinational, randomized, double-blind, phase IV study in 60 patients; follow-up was 1 month. There was a significant increase in cardiac index and a significant decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 17 publications
0
45
1
3
Order By: Relevance
“…This can result in increased myocardial oxygen consumption and myocardial Ca 2ϩ overload (30). Newer therapeutics target myofilament activation without altering the Ca 2ϩ transient, and these myofilament Ca 2ϩ sensitizers (e.g., levosimendan, Levo) and myosin activators (e.g., omecamtiv mecarbil, OM) are used to treat acute and chronic HF (5,20,37).…”
mentioning
confidence: 99%
“…This can result in increased myocardial oxygen consumption and myocardial Ca 2ϩ overload (30). Newer therapeutics target myofilament activation without altering the Ca 2ϩ transient, and these myofilament Ca 2ϩ sensitizers (e.g., levosimendan, Levo) and myosin activators (e.g., omecamtiv mecarbil, OM) are used to treat acute and chronic HF (5,20,37).…”
mentioning
confidence: 99%
“…In an updated meta‐analysis comprising six trials, we found no statistically significant difference in short‐term mortality,27, 28, 29, 30, 31, 32 long‐term mortality,27, 30, 31, 33, 34, 35 ischemic events,30, 34 acute kidney injury,31 dysrhythmias,30, 36 or hospital length‐of‐stay37 in patients with cardiogenic shock treated with dobutamine vs. levosimendan (Fig. 3, Fig.…”
Section: Resultsmentioning
confidence: 94%
“…А також частота виникнення шлу-ночкової тахікардії була вище, ніж при застосуванні добутаміну [9]. При застосуванні β-блокаторів че-рез 48 годин після початку 24-годинної інфузії ле-восимендану, вплив на гемодинамічні показники були кращі, ніж після 48-годинної інфузії добутамі-ну [11].…”
Section: Imr@ukrnetunclassified